2008
DOI: 10.1002/msc.137
|View full text |Cite
|
Sign up to set email alerts
|

Piloting education days for patients with early rheumatoid arthritis and their partners: A multidisciplinary approach

Abstract: The development of this 'local' education and information intervention was carried out in line with Medical Research Council guidelines, and the lessons learned from Day 1 informed further development for Day 2. A one-day format for education of early RA involving the rheumatology MDT was rated highly by participants and warrants further examination. Although this study was a small 'local' intervention, its strengths are that it informs the possibility of wider developments of this kind using a MDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
(15 reference statements)
0
19
0
2
Order By: Relevance
“…As shown in Table 2, 5 papers reported studies that recruited only older age groups (people aged 50 years and over [22][23][24], people aged 55 years and over [25], or people aged 65 years and over [26]), thereby likely excluding women of reproductive age. A further 10 studies did not report detailed eligibility criteria [27][28][29][30][31][32][33][34][35][36].…”
Section: Studies With Exclusion Criteria Related To Pregnancy Breastmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2, 5 papers reported studies that recruited only older age groups (people aged 50 years and over [22][23][24], people aged 55 years and over [25], or people aged 65 years and over [26]), thereby likely excluding women of reproductive age. A further 10 studies did not report detailed eligibility criteria [27][28][29][30][31][32][33][34][35][36].…”
Section: Studies With Exclusion Criteria Related To Pregnancy Breastmentioning
confidence: 99%
“…In a later unrelated study, Hammond and colleagues [42] evaluated a modular behavioural arthritis education program that included a facilitated discussion about the impact of arthritis on the family. Finally, the study by Ellard et al [34] evaluated the effect of targeted education for people with RA and their partners, provided in the form of day-long workshops. One of the workshops involved small-group discussions on relationships, led by a specialist registrar and a psychologist.…”
Section: Information About Relationships and Sexual Advicementioning
confidence: 99%
“…Patients expressed diffi culty following treatment/medication regimens. Ellard et al (2008) concluded that patients who participated in an informative 2-day program on rheumatoid arthritis expressed various positive outcomes, such as sharing experiences with others in similar situations, increased involvement in healthcare decision making, and instigating treatment changes.…”
mentioning
confidence: 97%
“…Наилучшая приверженность немедикаментозным методам через 3 мес и некоторое угасание эффекта обучения к 6-му мес подтвердили необходимость регулярного прове-дения «Школ здоровья». Полученные нами результаты согласуются с данными многочисленных исследований, показавших, что образова-тельные программы повышают уровень знаний о РА, само-эффективность пациентов, возможность самоконтроля над заболеванием, социальную адаптацию, приверженность стратегиям защиты суставов, способствуют снижению риска сердечно-сосудистых заболеваний, выработке правильного поведенческого стереотипа, использованию вспомогатель-ного бытового адаптивного оборудования и ортезов, регуляр-ным занятиям ЛФК [16][17][18][19][20][21][22][35][36][37][38][39]. Клинические рекомен-дации по немедикаментозному лечению РА (EULAR, ACR, British Society for Rheumatology и французские) считают обра-зовательные программы, направленные на поддержание тру-доспособности и функционального статуса, помогающие справиться с болью и снизить инвалидность, неотъемлемой частью комплексного ведения больных РА [23-25, 40, 41].…”
Section: о п р о с н и к д л я о ц е н к и п р и в е р ж е н н о с т unclassified
“…Не определены оп-тимальные сроки начала образовательных программ у паци-ентов с РА. В настоящее время в мировой литературе суще-ствуют небольшое число сообщений о положительном эф-фекте образовательных программ у больных ранним РА [16][17][18][19][20][21][22]. Выводы немногочисленных клинических рекомен-даций по обучению больных РА в ранней стадии экстрапо-лированы из результатов оценки эффективности образова-тельных программ при развернутом заболевании [23][24][25].…”
unclassified